Construction of risk prediction model and risk score table for infant heart failure hospital death based on white blood cell count to total protein ratio - Shuai Shang; Meng Wei; Huasheng Lv; Xiaoyan Liang; Yanmei Lu; Baopeng Tang (Heliyon)
The study analyzed 544 infants (1–36 months) with heart failure, aiming to correlate WBC/TP ratio with mortality and create a predictive model. Lasso regression identified significant mortality-associated clinical indices; logistic regression then built a death prediction model with an AUC of 0.755. Calibration and DCA curves indicated model accuracy and clinical utility. Risk stratification revealed higher mortality in the high-risk group, emphasizing WBC/TP as predictors and the model's value for early high-risk patient identification in infant heart failure.